An Integrative Model of Managerial Reward Allocation,, - Freedman, Sara M.; Montanari, John R. (Academy of Management Review, 1980)
An understanding of the variables that affect managerial reward allocation decisions is vital because of the effects of such rewards on employee behavior and organizational effectiveness. We present an integrative model of the reward allocation process in organizations, review previous research within the framework of the model, and suggest areas for future research.